2019
DOI: 10.2478/udt-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

On the Intriguing Search for Good Permutations

Abstract: The intriguing search for permutations that generate generalised van der Corput sequences with exceptionally small discrepancy forms an important part of the research work of Henri Faure. On the occasion of Henri’s 80th birthday we aim to survey (some of) his contributions over the last four decades which considerably improved our understanding of one-dimensional van der Corput sequences and inspired a lot of related work. We recall and compare the different approaches in the search for generalised van der Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This question, originally due to van der Corput, was answered by van Aardenne-Ehrenfest who showed that no such result exists; see [15] for details. The problem was finally solved by Schmidt [23] who proved that D N ≥ cN −1 log N for infinitely many N ∈ ℕ ; see [12,15,20,23] and references therein as well as [16,17] for the currently best constants. Sequences with D N (X) ≤ cN −1 log N for a constant c > 0 and all N are called low discrepancy sequences.…”
Section: A Problem In Combinatorics and Number Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This question, originally due to van der Corput, was answered by van Aardenne-Ehrenfest who showed that no such result exists; see [15] for details. The problem was finally solved by Schmidt [23] who proved that D N ≥ cN −1 log N for infinitely many N ∈ ℕ ; see [12,15,20,23] and references therein as well as [16,17] for the currently best constants. Sequences with D N (X) ≤ cN −1 log N for a constant c > 0 and all N are called low discrepancy sequences.…”
Section: A Problem In Combinatorics and Number Theorymentioning
confidence: 99%
“…The original definition of the van der Corput sequence is based on writing integers in binary expansion: the n− th element is given by (1) writing the integer in binary, i.e. 22 = 10110 2 (2) inverting the order of the digits 10110 → 01101 (3) writing a comma in front of it and interpreting it as a real number in [0,1] The van der Corput sequence and its various generalisations are known to be very close to optimal with regards to discrepancy; see [11,12,20].…”
Section: A Problem In Combinatorics and Number Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…for every point in the solution space. To calculate what this number is, the number of permutations possible within our paths must be calculated [46], using…”
Section: Path Determinationmentioning
confidence: 99%
“…That is, f * is the supremum over all c such that ( * ) holds. Study in areas of the same flavour have appeared recently in the form of asympototic constants of the corresponding notions of (star and extreme) discrepancy [12,13,15,16]. Returning to our motivation, in his 1986 paper Proinov states a lower bound for f * .…”
Section: Introductionmentioning
confidence: 98%